Clinical Outcomes of Minimally Invasive and Traditional Approaches in Perforated Peptic Ulcer Management (Asian Journal of Pharmaceutics (AJP), 2025)
Background: Laparoscopic surgery has emerged as a promising alternative to traditional open repair forperforated peptic ulcer (PPU). Objective: This retrospective comparative study aimed to evaluate the clinicaloutcomes of laparoscopic and open surgical repairs in a tertiary care setting. Methods: Eighty-two patientswith perforated gastric or duodenal ulcers were included, with 32 undergoing laparoscopic surgery (Group I)and 25 undergoing open surgery (Group II) based on stringent inclusion criteria. Laparoscopic repair involveda diagnostic laparoscopy, ulcer closure with single-layer sutures, and omentopexy, which was performed. Opensurgery was performed through midline laparotomy with a similar ulcer closure. Postoperatively, both groupsreceived antibiotics, pain relief, and early mobilization therapy. Results: Group I had a significantly shorterhospital stay (3.8 ± 0.38 days vs. 6.9 ± 0.75 days, P < 0.001) and quicker oral intake resumption (1.6 ± 0.5 daysvs. 2.8 ± 0.8 days, P = 0.002) than Group II. The incidence of post-operative complications was lower in Group I(3.1% vs. 12.0%, P = 0.03). No surgical site infections, pneumonia, reoperations, or mortality occurred in Group I.Conclusion: These findings suggest that laparoscopic repair is a safe and effective alternative to open surgeryfor PPUs in selected patients, offering shorter hospital stays, fewer complications, and faster recovery. However,careful patient selection based on perforation size, location, presentation time, and comorbidities is crucial forsuccessful outcomes. Further prospective multicenter studies are needed to confirm these results and establishguidelines for wider clinical applications, particularly in resource-limited settings.